PENGARUH GCG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Dea Tiara Monalisa Butar-Butar (Journal of Global Business and Management Review, 2022)
This study aims to examine the effect of Good Corporate Governance and profitability on firm value in manufacturing company listed in Indonesia Stock Exchange on period 2017-2021. GCG was represented with independent commissioners, institutional ownership, and audit committee. The sampling technique used was purposive sampling. The analytical method is panel data regression using a fixed affect model. The results of this study indicate that the proportion of independent commissioners and managerial ownership has a significant and positive effect on firm value, while institutional ownership, audit committee, and return on assets (ROA) have no significant effect on firm value.